Influential Factors of Travel Bubbles Intention During COVID-19 among Cambodians in Siem Reap and Preah Sihanouk - So, Visothy (Scholar: Human Sciences, 2023)
Purpose: Travel bubbles, as the arrangements by the participant countries to open up their frontiers for travelers from partner destination or regions, has been widely implemented during COVID-19. Hence, this study aims to examine the influential factors of travel bubbles intention during COVID-19 among Cambodians in Siem Reap and Preah Sihanouk. The conceptual framework contains perceived usefulness, government support, innovativeness, trust, perceived risk, social influences, price value, and behavioral intention. Research design, data, and methodology: This quantitative study was distributed to 500 participants with a questionnaire. The sampling techniques involve judgmental, convenience, and snowball sampling. The Item Objective Congruence (IOC) Index and Cronbach’s Alpha coefficient value of the pilot test of 42 respondents were assessed before collecting the data. Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) are applied. Results: The results are that government support, trust, perceived risk, and social influences significantly influence, whereas perceived usefulness, innovativeness, and price value have no significant influence on behavioral intention to adopt travel bubbles. Conclusions: Travel agencies and hospitality should strategize their businesses in response to the new type of measure due to the new normal for every individual being enforced and the new tourism trend being shaped.